Utility of chest ultrasound and intrapleural fibrinolytics with gentamicin following failed pleurodesis - Aldo Pezzuto; Ferdinando Cozzolino; Giosuè Amoroso; Evohe Adone; Elisa Desideri; Alberto Ricci (Monaldi Archives for Chest Disease)
This is a case of a 65-year-old male patient who presented to our institution due to worsening dyspnea and respiratory failure development. The patient was admitted due to dyspnea at rest and chest pain. He had a recent medical history of lung cancer with malignant pleural effusion. The patient had already undergone pleural talc poudrage by thoracoscopy, which had not been effective. Indeed, the patient was found to have residual septate pleural effusion on ultrasound examination. A placement of transthoracic pleural drainage followed by intrapleural instillation of urokinase (100,000 units) and gentamicin (80 mg) was performed within 30 days of chemical pleurodesis, achieving re-expansion of the lung by preventing recurrence of the effusion and leading to rapid clinical improvement. The novelty of the present case concerns the effectiveness of a combined treatment of fibrinolytic and intrapleural antibiotic through a pleural drainage after failure of chemical pleurodesis.